2015
DOI: 10.1007/3418_2015_112
|View full text |Cite
|
Sign up to set email alerts
|

Pincerlike Cyclic Systems for Unraveling Fundamental Coinage Metal Redox Processes

Abstract: Pincerlike cyclic ligands have overcome the high instability of transition metals in their higher oxidation states and have permitted the isolation of such species and the exhaustive study of their properties and reactivity. The formation and isolation of organometallic Cu II and M III (M¼Cu, Ag, Au) complexes stabilized by NCPs, carbaporphyrins, carbaporphyrinoids, heterocalixarenes, and triaza macrocyclic ligands will be discussed in this chapter. The study of these complexes have led to the discovery of unp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…The clear-cut distinction between the reactivity of boronic acid with organocopper­(II) and organocopper­(III) compounds was not expected. Our previous studies have shown that azacalix­[1]­arene­[3]­pyridine-derived arylcopper­(III) complexes exhibit remarkable reactivity toward diverse nucleophiles ranging from halides, acetates, aryloxy and alkoxy, nitrate and amides, and thiocynate and cyanide to alkyl and alkynyl lithium reagents. , An analogous cross-coupling reaction property has also been observed by Stahl and Ribas ,, for a similar macrocyclic arylcopper­(III) species which is derived from a m -phenylene-embedded azacrown ether . It should be addressed that the outcomes of the stoichiometric reactions of high valent arylcopper compounds with arylboronic acid were very important in comprehending the mechanism of catalysis.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…The clear-cut distinction between the reactivity of boronic acid with organocopper­(II) and organocopper­(III) compounds was not expected. Our previous studies have shown that azacalix­[1]­arene­[3]­pyridine-derived arylcopper­(III) complexes exhibit remarkable reactivity toward diverse nucleophiles ranging from halides, acetates, aryloxy and alkoxy, nitrate and amides, and thiocynate and cyanide to alkyl and alkynyl lithium reagents. , An analogous cross-coupling reaction property has also been observed by Stahl and Ribas ,, for a similar macrocyclic arylcopper­(III) species which is derived from a m -phenylene-embedded azacrown ether . It should be addressed that the outcomes of the stoichiometric reactions of high valent arylcopper compounds with arylboronic acid were very important in comprehending the mechanism of catalysis.…”
Section: Resultsmentioning
confidence: 59%
“…Since the Cu­(II)/Cu(0) catalytic cycle in Figure was excluded, the aryl–aryl coupling is most likely to occur via reductive elimination from the diaryl copper­(III) intermediate B . Concurring with the documented results of the reactions of high-valent organocopper­(III) complexes, ,, , , the reductive elimination from diarylcopper­(III) complex B was calculated to be almost barrierless (Figure S15 in the Supporting Information). Therefore, the central question was focused on the intriguing step of transmetalation of a boronic acid to organocopper species.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…[1][2][3][4][5] However, there is continuous need to discover new synthetic tools in order to have in hand versatile solutions for a given cross-coupling transformation. Silver has been completely forgotten in its use as catalyst for cross-coupling, [6][7] which typically undergoes 2-electron redox processes, since it is generally believed that Ag only shows 1-electron redox chemistry. [8][9] Nevertheless, albeit scarce, there are reports showing that silver catalyzes Sonogashira-type couplings 10 and Ullmann-type C-N and C-O couplings, 11 although with complete lack of mechanistic understanding.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Interestingly,t he importanceo fA g(III) intermediates in silver-catalyzed CÀX, CÀC, CÀN, and CÀOc rosscouplings was recentlyd emonstrated. [14] The handful of organosilver(III) compounds currently known are only stabilizedb y eitherm acrocyclic ligands [15] or by fluorinated methyl groups. [16] In fact, the non-fluorinated complexes [(CH 3 ) 3 AgI] À and [(CH 3 ) 4 Ag] À were found to be unstable.…”
Section: Dedicatedtodrm Ilagros Tomµso Nthe Occasion Of Her 65th Birmentioning
confidence: 99%